Fizika polarnega sija - Tegeltija, David (Matrika, 2022)
Aurora polaris, commonly known as the polar lights is an expression used to describe the natural light display in the Earth’s sky, typical for the arctic circle. The phenomenon can occur on the North or South pole and is not exclusive for planet Earth. On the contrary, it has been observed on other planets in our Solar System. The origin for this phenomenon comes from the collision between high-energy particles from outer space, trapped inside a magnetic field, and a planet’s own magnetic field. In the case of planet Earth, the Sun is the source of such particles. The colliding magnetic fields interact with eachother and consequently the aforementioned high-energy charged particles reach the planet‘s atmosphere where they give their excess energy to surrounding atoms and molecules in that athmosphere. With this, they excite them into higher quantum states. The excited atoms and molecules then emit their excess energy in the form of photons that can be in the visible spectrum which we then see as the polar lights.
Keywords: Earth magnetic field; polar lights; polarni sij; Zemljino magnetno polje